How to Make the Right Choice of Proton Pump Inhibitor for Patients with Gastroesophageal Reflux Disease? - Yu. V. Evsyutina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to analyze the main pharmacokinetic properties of proton pump inhibitors (PPIs) and their significance in the treatment of gastroesophageal reflux disease (GERD).Key points. Pantoprazole has a high bioavailability, the absolute bioavailability of pantoprazole at a dose of 40 mg is 77 % from the first dose and does not change with repeated use. Pantoprazole shows a faster onset of action than omeprazole. Simultaneous food intake does not change the bioavailability of pantoprazole. Suppression of hydrochloric acid production while taking pantoprazole accompanies by the achievement of endoscopic remission of GERD by day 28 in 91 % of patients with reflux esophagitis and by day 56 in all patients in the PANSTAR studies. Pantoprazole has little effect on CYP2C19 compared to other PPIs, minimizing the risk of drug-drug interactions. Pantoprazole is the most pH-selective PPI, which determines the specificity of action only in the parietal cells of the stomach and the greatest safety of long-term use in patients with comorbid pathology.Conclusion. PPIs form the basis of the therapy of acid-dependent diseases, and, in particular, gastroesophageal reflux disease. Pantoprazole is distinguished from other PPIs by its persistent high bioavailability, long-term antisecretory effect, and very low affinity for cytochrome P450.